INFRASTRUCTURE FOR THE MEDICAL CARE OF PATIENTS WITH IBD IN THE REPUBLIC OF IRELAND; PRELIMINARY RESULTS OF A NATIONAL ELECTRONIC SURVEY. (8th June 2013) - O'Connor, A; Egan, B; Forry, M; Keohane, J; Jackson, L; Egan, L; Doherty, G
Abstract : Introduction: The UK National IBD Audit (now in its fourth cycle) has focused attention on quality of care for IBD patients and has lead to the generation of agreed national standards of care in the UK. Aims/Background: This project was performed to gather baseline information on the infrastructure for care of patients with IBD in Ireland using elements adapted from the UK National IBD Audit. Method: An invitation to participate in an electronic survey was distributed by post and e-mail to Consultant Gastroenterologists and ISG members in the Republic of Ireland. The survey was conducted by an independent market research organization. Results: n=13 responses were received; 4 responses from HSE hospitals, 4 responses from public voluntary hospitals, 5 responses from private centres. Only 4/13 (31%) of centres have an identified ward for the care of hospitalised patients with IBD. In 7/13 cases, the ratio of beds to lavatories for in-patients exceeds 3 (maximum 7 beds). All respondents rated the role of the IBD nurse as important or very important in the care of IBD patients. 11/13 reported somewhat or very limited access to magnetic resonance enterography (MRE) for small bowel imaging; 5/13 respondents reported out-patient waiting times exceeding 12 weeks for MRE. Most centres highlighted a lack of IBD nurses, IBD specialists and waiting times for diagnostic tests as important current barriers to optimal care for IBD patients. Conclusion: Preliminary results of the first national survey of the infrastructure for care of IBD patients have highlighted important areas for improvement. The ratio of beds to lavatories on in-patient wards recommended by the UK National IBD standards is exceeded in most centres. There is poor access to MRE in many sites, leading to avoidable exposure to ionising radiation. The survey emphasises the importance of the IBD nurse specialist in patient care. The findings identify priority areas for improving the quality of care for IBD patients in the Republic of Ireland.